Exploring the economic essence of cryptocurrencies: advantages and disadvantages - Mekhovych, Ye. S. (Teadmus OÜ, Tallinn, 2025)
The report substantiates that cryptocurrencies are a unique financial phenomenon that continues to evolve and change the global economic landscape. They provide users with new opportunities to conduct financial transactions, increasing speed, transparency and reducing transaction costs. At the same time, their decentralized nature contributes to reducing dependence on traditional financial institutions, which makes cryptocurrencies especially attractive in conditions of economic instability.
Keywords: cryptocurrency; digital money; financial transactions; legalization; efficiency; efficiency; legislative consolidation